ANALYSIS OF HEALTH SERVICE QUALITY ON PATIENT SATISFACTION IN IMPROVING XYZ HOSPITAL SERVICES - Heriyanto Heriyanto; Iwan Vanany; Imade Jiwa Astika; Sutrisno Sutrisno (JOURNAL ASRO, 2022)
XYZ Hospital is a type c military hospital located in Surabaya and has the function of support and optimal health services for military personnel, military families, and the general public. In its implementation, there are several problems related to health services including a decrease in the number of patient visits, a lack of human resources, and long patient service times. Therefore, it is necessary to analyze the quality of health services in improving XYZ hospital services. The method approach used covers Service Quality (Servqual) is used To look for performance gaps, Importance Performance Analysis (IPA) used to know the level of suitability perceptions and expectations of health services hospitals, and Quality Function Deployment (QFD) through the house of quality (HOQ) for determining priority a must repair done. Based on research results of 99 respondents show of 5 dimensions Servqual obtained a valuable performance gap positive namely 3 attributes E1-X7, E4-X10, A3-X27 and a value negative namely 27 attributes R2-X20, R4-X22, RE1-X12, RE3-X14, R5-X23, A5-X60, A1-25, T4-X4, A2-X26, T1-X1, RE5-X16, R3-X2, RE7-X18, T5-X5, RE2-X13, T3-X3, E5-X11, R1-X19, R6-X24, T2-X2, A4-X28, T6-X6, RE6-X17, A6-X30, RE4 -X15, E3-X9 and E2-X8. After analysis with the IPA, the method obtained Quadrant I 10 attributes that is T5-X5, RE1-X12, RE3-14, RE5-X16, RE7-X18, R4-X22, R5-X23, R2-X20, A1-X25, A5- X29 being priority repair service health, quadrant II 6 attributes that show keep it up performance T1-X1, T4-X4, RE4-X15, R1-X19, A2-X26 and A6-X30 quadrant III 8 attributes considered not enough important for patients and services received considered ordinary and quadrant IV 6 attributes. considered not enough important for patients however services provided too much. Analysis next uses the QFD method to create HOQ to determine the originating voice of the customer from IPA analysis in quadrant I and Quadrant II, as well as response technical repair to service such, so, got 3 responses technical as priority repair. First, 15% target responsiveness to the patient service process done with good Health training and training on an ongoing basis scheduled, both 13% target responsiveness to the use of system information management hospital, and the third target is 11 % reliability to Settings timetable practice doctor.